Communication skills and positive mental health in the professional profile of teachers in basic education of Lima - Orellana Manrique, Oswaldo (2012)
This research selects two variables contributing to the configuration of a teacher profesonal profile public education, psychology, and from communication skills and positive mental health, the latter focusing on six factors: personal satisfaction Prosocial Attitude; self-control, autonomy, and self-actualization Troubleshooting, and interpersonal skills, explored by the variable positive mental health and communicative competence, identifying thinking styles resulting from cerebral hemispheric dominance. The sample consisted of 274 teachers of different levels of basic education and working in the geographical scope of the department of Lima, as controlled variables that favor the correlation analysis of the variables investigated The findings found thick, require that scores of communication skills (tests 1 and 2) have significant correlations with positive mental health reaching 0.197, 0.190, 0.67, 0.175, and in the opposite case of test scores 3 and 4 which show virtually no correlation with positive mental health., which means that cross dominances evidence of the cerebral hemispheres that guide communicative communication regarding positive mental health, highlighting almost uniformly left and right hemispheres. We conclude that there is a dominance of the left hemisphere and upper brain, did a profile predisposing logical-rational-logical analytical and creative, in the first case allows a process of verbal communication and writing characterized by a symbolic language and argumentative ideal for scientists test development that prevail in the elaborate codes of science discourse. However it is necessary to note that the profile is dogmatic and reductionist, and the second allows a process of communication both verbal and nonverbal, for in that profile gives half a communication between the two hemispheres through the corpus callosum. Because there are synergistic capacity but reduced capacity to act both in the body of scientific test as in poetry, the story is a profile yet neglecting the humanities, the spiritual and the management of human complexity. Importantly, positive mental health, specifically item 20 "I think I'm a people person" has significant and negative correlations with the four test scores of communication skills, recommending further analysis of the results obtained in the present contrasting research with other research, thus contributing to a better understanding of the communicative competence with positive mental health.